2006
DOI: 10.1002/cyto.b.20152
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1‐infected children on HAART: Immunologic features of three different levels of viral suppression

Abstract: Background: HIV-1-infected children show changes of blood lymphocyte subpopulations. We have, therefore, investigated how highly active anti-retroviral therapy (ART) alter these subsets. Blood samples were taken from 41 HIV-1-infected children on ART who were divided into groups showing good, partial and poor responses to ART on the basis of viral load (VL) measurement in blood. The observations were compared to those seen in 20 uninfected children.Methods: The samples were studied using 4-color flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
1
19
0
3
Order By: Relevance
“…ZaccarelliFilho et al (15) have also reported high basophil numbers in HIV-infected children. These cells are known to be elevated in conditions associated with Th2 responses (16).…”
Section: Discussionmentioning
confidence: 92%
“…ZaccarelliFilho et al (15) have also reported high basophil numbers in HIV-infected children. These cells are known to be elevated in conditions associated with Th2 responses (16).…”
Section: Discussionmentioning
confidence: 92%
“…Three patients, in whom tetanus toxoid-specific proliferation was measured before booster vaccine, regained specific proliferation indicating an immune reconstitution through effective ART without any booster. Zaccarelli-Filho et al (38) also observed low levels of vaccine specific antibodies in HIV-infected children, whereas other authors also observed good revaccination results concerning tetanus (39), measles, mumps, and rubella (40) and other live attenuated vaccines (41)(42)(43)(44) in most children on ART.…”
Section: Discussionmentioning
confidence: 98%
“…51 For tetanus and diphtheria toxoids, positive responses are indicated by ELISA with a minimal cut-off of 0.01 IU/mL with optimal levels of 0.1 IU/mL or by LPA with SI above 3. 52,53 numbers of functional memory B-cells in this population including HIV-1 specific responses. [36][37][38][39] However, currently HIV-1 infected children in developing countries do often have access to HAART late in childhood and receive some of the routine immunizations, i. e. against tuberculosis, poliomyelitis, diphtheria, tetanus and pertussis, within the first weeks of life before being treated, most likely, when ongoing HIV-1 replication reaches its highest level.…”
Section: Immune Reconstitution and Vaccination Outcome In Hiv-1 Infecmentioning
confidence: 99%
“…53 Duration of HAART has also been shown not to play a major role in relation to vaccine responses to tetanus toxoid. 59 However, we have shown that antibodies to tetanus toxoid remain high (to levels comparable to age-matched healthy individuals) for several years after DTP in children treated with HAART before 1 y of age compared with children also having Many studies on DTP (mostly analyzing immunity to tetanus toxoid) involving re-vaccination of children on HAART are available.…”
Section: Adaptive Immune Response To Different Vaccine Typesmentioning
confidence: 99%
See 1 more Smart Citation